Similarities and differences: a preliminary comparative study of Arabic and Kadazandusun phonology - Mohd Taqwudin Mohd Yazid; Veronica P. Atin (Human Resource Management Academic Research Society (HRMARS), 2019)
Arabic is one of the languages that is offered as a foreign language to learners who have never learned the language before studying in UMS. Takers of the language include learners of the Kadazan/dusun ethnic groups who speak either any dialect of Kadazan/Dusun, Sabah Malay, or English as their first language. The study compares some phonological aspects of Arabic and Kadazandusun with the objectives of identifying the differences between the phonological systems of Arabic and Kadazandusun, and suggest how the differences might be affecting learners of Kadazandusun who learn Arabic as a foreign language. The findings show that Arabic and Kadazandusun share three similar vowels, but Arabic has twelve consonants that are different than Kadazandusun. Apart from that, in Arabic vowel alterations can carry grammatical functions such as plurality which do not exist in Kadazandusun. The authors suggest some areas of difficulties for Kadazandusun learners in learning Arabic, and recommended further studies to confirm the suggestions, as well as to propose learning strategies for learners to cope with the difficulties.